ECONOMIC EVALUATION OF THE ELECTRONIC PUBLIC PROCUREMENT SYSTEM: THE CASE OF PROZORRO 2018-2022 - Dluhopolskyi, Oleksandr; Danyliuk, Iryna (Socio-economic relations in the digital society, 2023)
The paper examines savings in the system of public cigarette lighters in 2018-2022 in terms of key product groups: gasoline, flour, eggs, potatoes, milk, sugar. It is substantiated that the introduction of ProZorro electronic competitive procedures has a positive effect of savings on the analyzed types of products in almost all the studied years due to the fact that the purchase price was ultimately lower than the average market prices. The median margin has shown unstable values throughout all years, this situation is explained by the dispersion of prices and the variety of purchases. In general, according to the results of the study of selected homogeneous goods, which collectively constitute 0.007% of all purchases by the amount of concluded contracts for 2018-2022, it turned out that the electronic procurement system of ProZorro gives a significant effect of savings, and the cumulative difference between the actual cost of the purchase and the market value - increases starting from 2021. In the conditions of monopolization of prices, the economic effect of using ProZorro is much weaker or absent, and the reduction of corruption rent cannot always be achieved exclusively at the expense of procurement transparency, because in some cases there is a threat of non-competitive bidding. That is why competitiveness through the ProZorro system is the best way to save money in the budget sphere.